Respuesta :

Answer:

4

Step-by-step explanation:

f(x) = 1/2 *[tex]x^{2}[/tex] + 2x - 5

f'(x) = d/dx (1/2 * [tex]x^{2}[/tex] + 2x - 5)

=d/dx 1/2 *[tex]x^{2}[/tex] + d/dx 2x - d/dx 5

d/dx 1/2 * [tex]x^{2}[/tex] = x  [Because to differentiate a exponential, you multiply the coefficient by the exponent (1/2 * 2) and then subtract 1 from the exponent: 2-1 = 1]

d/dx 2x = 2 [same as the explanation above]

d/dx 5 = 0 [differentiating a constant always equals zero]

so f'(x) = x+2

so f'(2) = 2+2 =4

ACCESS MORE